Challenges in management of the company's corporate social responsibility in medical business - Kovshik, V. I.; Li, Hongjie (Державний біотехнологічний університет, 2024)
The paper examines the specifics of corporate social responsibility (CSR) management in healthcare businesses under globalization and increasing societal demands. Key CSR dimensions are identified, including environmental, ethical, philanthropic, and economic responsibility, as well as their contribution to sustainable development goals. The study emphasizes unique challenges faced by medical organizations: regulatory complexity, limited financial resources, ensuring equal access to healthcare, high stress levels and burnout among employees, and the need for effective stakeholder engagement. It is concluded that healthcare companies require tailored CSR policies and further research on the relationship between CSR performance and internal and external environmental factors to enhance competitiveness.

У роботі розглянуто особливості управління корпоративною соціальною відповідальністю (КСВ) у медичному бізнесі в умовах глобалізації та зростання вимог суспільства. Визначено основні напрями КСВ: екологічна, етична, філантропічна та економічна відповідальність, а також їхній внесок у досягнення цілей сталого розвитку. Підкреслено специфічні виклики медичних підприємств: регуляторні обмеження, дефіцит фінансових ресурсів, необхідність забезпечення рівного доступу до медичних послуг, високе професійне навантаження працівників та проблеми вигорання. Зроблено висновок про необхідність розробки окремих політик КСВ для медичного сектору та подальших досліджень щодо взаємодії із зацікавленими сторонами для підвищення конкурентоспроможності.
Keywords: корпоративна соціальна відповідальність; сталий розвиток; медичний бізнес; управління; corporate social responsibility; sustainable development; healthcare business; healthcare business; management; business ethics